Ultra-flexible and high-sensitive triboelectric nanogenerator as electronic skin for self-powered human physiological signal monitoring. (March 2020) - Yu, Junbin; Hou, Xiaojuan; He, Jian; Cui, Min; Wang, Chao; Geng, Wenping; Mu, Jiliang; Han, Bing; Chou, Xiujian
Abstract: Electronic skin (E-skin) with tactile sensing characteristics has presented great potential in disease diagnosis and health assessment; however, the imperfect combination of ultra-flexibility and high-sensitivity have restricted its widespread application. Here, we report a contact-separation triboelectric-nanogenerator (CS-TENG) consisting of ultra-flexible micro-frustum-array polydimethylsiloxane (mf-PDMS) film and Cu electrodes as the basic friction units, which can achieve self-powered weak physiological signal monitoring with great comfort. The CS-TENG uses elastic mf-PDMS as both the major body and the friction layer to realize ultra-flexible and conformal contact with irregular human skin. By exploring the microelectromechanical system (MEMS) preparation process, a uniform and controllable mf-arrays structure was fabricated to utilize both the normal and shear stresses, thereby increasing friction and enhancing device sensitivity. The CS-TENG displays high sensitivity (5.67 V/10 5 Pa), good linearity ( R 2 = 0.99 of voltage), high stability (more than 80000 cycles), and fast response time (60 ms). With these outstanding characteristics, the CS-TENG can sense subtle changes in wrist pulse under various physiological conditions, which can also be easily arranged into a 1 × 3 array to mimic the three-fingered pulse-taking in traditional Chinese medicine. This work provides a new way to prepare ultra-flexible and high-sensitive TENG as E-skin and demonstrates its potential application. Graphical abstract: A novel ultra-flexible micro-frustum-arrays-PDMS based contact-separation triboelectric nanogenerator (CS-TENG) was reported as self-powered Electronic skin, which shows high sensitivity, high stability, good linearity and fast response time. The CS-TENG realizes conformal contact with the complex texture of the irregular skin and presents great potential in disease diagnosis and health assessment as well as the fusion of TCM and modern medicine. Image 1 Highlights: The uniform, controllable and super small micro-frustum-arrays structure (mf-structure) was fabricated by MEMS technology. The mf-structure could increase the effective friction and then improve the output performance. The sensor uses mf-PDMS as both the major body and friction layer to realize conformal contact with the irregular skin. The sensor brings the spring for modern medicine, traditional Chinese medicine and disease diagnosis.